2020
DOI: 10.3390/ijerph17134889
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of Knowledge about Oral Cancer in Italy: A 505 Person Survey

Abstract: Objectives: Patients’ knowledge about oral squamous cell carcinoma (OSCC) plays an important role in primary prevention, early diagnosis, and prognosis and survival rate. The aim of this study was to assess OSCC awareness attitudes among general population in order to provide information for educational interventions. Methods: A survey delivered as a web-based questionnaire was submitted to 505 subjects (aged from 18 to 76 years) in Italy, and the answers collected were statistically analyzed. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
5
17
0
1
Order By: Relevance
“…This may be due to the population's little knowledge on oral cancer, its risk factors, and its specific characteristics, leading them to neglect the initial signs and symptoms and, consequently, delay in the search for specialized care. This fact corroborates another study ( 31 ) that concluded that the population, even knowing the existence of oral cancer, does not have enough information for the correct diagnosis and prevention of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…This may be due to the population's little knowledge on oral cancer, its risk factors, and its specific characteristics, leading them to neglect the initial signs and symptoms and, consequently, delay in the search for specialized care. This fact corroborates another study ( 31 ) that concluded that the population, even knowing the existence of oral cancer, does not have enough information for the correct diagnosis and prevention of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, there is a different level of awareness about risk factors. Subjects correctly identified smoking as the major risk factor (94.1%), consistently with the data obtained in our previous campaign among preadolescents (92.2%), and in a higher proportion compared with studies performed in Italy (32) and in other areas (22-24). Such data may suggest that previous campaigns performed on the territory were effective in informing and educating in identifying tobacco smoking as a risk factor for several cancer types, including OSCC in both younger and older subjects.…”
Section: Principal Findings and Comparison To Other Studiessupporting
confidence: 89%
“…La detección temprana de lesiones potencialmente maligna 58 , evita su desarrollo hacia fases avanzadas de la enfermedad, que oscurecen su pronóstico, por medio de una atención rápida y adecuada, biopsia oportuna, y tratamiento precoz, evitando que los pacientes sufran o mueran por esta causa 42 . Se informa en la literatura que el 58% de los retrasos fueron causados por la postergación de los pacientes en consultar a los profesionales de la salud, y que esto podría resultar en unos 1,6-5,4 meses de retraso en el diagnóstico [64][65][66] . Este aplazamiento está fuertemente relacionado con la falta de conocimiento de los pacientes sobre temas del cáncer bucal.…”
Section: Discussionunclassified